2019
DOI: 10.3382/ps/pez190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different types and levels of fat addition and pellet binders on physical pellet quality of broiler feeds

Abstract: Two experiments were conducted to evaluate the effects of different types and levels of mixer-added fat (soybean oil: SO and calcium fat powder: CFP) and pellet binders (PBs: calcium lignosulfonate (CaLS) and bentonite (Ben)) on physical pellet quality (PPQ) parameters. PPQ included pellet durability index (PDI), pellet hardness, and pellet length of broiler diets processed under short-term conditioning. The first experiment had 4 treatments arranged as a 2 × 2 factorial with 2 types (SO and CFP) and 2 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Bentonite as good as binder type with molasses because of water content inside feed ingredient as a matter of feed pellet. Other experiment also reported that adding pellet binder 0 to 3 % significantly improved pellet durability index (PDI) [17] Using molasses 5% doses has highest effect on pile density and pile compaction density. It also effect to highest durability pellet value.…”
Section: The Physical Quality Of Pellet Feedmentioning
confidence: 88%
“…Bentonite as good as binder type with molasses because of water content inside feed ingredient as a matter of feed pellet. Other experiment also reported that adding pellet binder 0 to 3 % significantly improved pellet durability index (PDI) [17] Using molasses 5% doses has highest effect on pile density and pile compaction density. It also effect to highest durability pellet value.…”
Section: The Physical Quality Of Pellet Feedmentioning
confidence: 88%
“…With a reduction of ∼30% of the oil content in the finisher diets in treatments 5 and 9, the pellet hardness was the highest (2.6 and 2.3 kPa, respectively) and about double the pellet hardness of the control treatment. Studies on the relation between added oil/fat content in the diet and pellet quality have reported that 3 to 6% added oil is ideal for optimizing pellet durability without excessive pellet hardness ( Briggs et al, 1999 ; Moritz et al, 2002 ; Mohammadi et al, 2019 ); pellet integrity is significantly compromised when the oil content surpasses 7.5% ( Briggs et al, 1999 ). Thus, the reduction in oil content in the low AME diets resulted in acceptable pellet quality.…”
Section: Discussionmentioning
confidence: 99%
“…The notable fat content of BSFL significantly influences poultry feed formulation, necessitating adjustments in nutrient balance and energy density [46]. This high level of fat can also impact pellet processing, affecting aspects such as pellet stability and nutrient preservation [47]. Consequently, incorporating BSFL into poultry diets requires careful consideration of these factors.…”
Section: Biochemical Profile Of Bsf Larvaementioning
confidence: 99%